2009
DOI: 10.1002/jrs.2461
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectra of the layered monofluorophosphate (V), NH4Ag3(PO3F)2

Abstract: The powder Fourier-transform (FT) infrared (IR) and Raman spectra of the recently characterized NH 4 Ag 3 (PO 3 F) 2 were recorded and are discussed with a site-symmetry analysis based on its known structural data. Some comparisons are made with the solution spectra of the PO 3 F 2− anion and with those of crystalline Ag 2 PO 3 F.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
(12 reference statements)
2
3
0
Order By: Relevance
“…The spectrum of 1 also shows some additional bands characteristic for the NH 4 + group. A broad band at 3217 cm –1 is attributed to the N–H stretching vibrations, while the band at 1406 cm –1 is ascribed to the N–H deformation vibrations. , The spectrum of 3 differs from those of 1 and 2 because this compound contains the PO 3 F group instead of the PO 3 (OH) group. A band at 1109 cm –1 , having a shoulder at the higher energy side of the band, is assigned to the asymmetric P–O stretching vibrations of the PO 3 F group.…”
Section: Results and Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The spectrum of 1 also shows some additional bands characteristic for the NH 4 + group. A broad band at 3217 cm –1 is attributed to the N–H stretching vibrations, while the band at 1406 cm –1 is ascribed to the N–H deformation vibrations. , The spectrum of 3 differs from those of 1 and 2 because this compound contains the PO 3 F group instead of the PO 3 (OH) group. A band at 1109 cm –1 , having a shoulder at the higher energy side of the band, is assigned to the asymmetric P–O stretching vibrations of the PO 3 F group.…”
Section: Results and Discussionsupporting
confidence: 79%
“…A band at 835 cm –1 is ascribed to the P–F stretching vibration. In the spectra of other monofluorophoshate compounds, the P–F stretching vibration band is found at 824 cm –1 for Hg 2 PO 3 F, 792 cm –1 for Ag 2 PO 3 F, and 776 cm –1 for NH 4 Ag 3 (PO 3 F) 2 . These results are in agreement with the structural features of the above-mentioned compounds, as the P–F bond length increases from 1.568(8) Å for Hg 2 PO 3 F through 1.575(2) Å for Ag 2 PO 3 F to 1.590 Å for NH 4 Ag 3 (PO 3 F) 2 . From the data provided, it can be concluded that the band shifts to the lower wavenumber with the P–F bond elongation.…”
Section: Results and Discussionsupporting
confidence: 79%
“…The IR spectra (Figure SI-2) of the title compounds 1 – 4 were recorded in the region of 4000–400 cm –1 . For the ammonia containing manganese phosphates ( 2 , 4 ), the vibration modes of the N–H bonds of the (NH 4 ) + ions range between 1384 and 1546 cm –1 (deformation vibrations) and 2784 and 3385 cm –1 (stretching vibrations). The broad band observed around 3225 cm –1 can be attributed to the stretching vibration of hydroxyl groups of the phosphate tetrahedra in all title compounds 1 – 4 . At lower wavenumbers, all IR spectra are quite similar because the vibrational modes for the P–OH, P–O, and P–F bonds of the various tetrahedral phosphate units (PO 2 (OH) 2 , PO 3 (OH), PO 3 F) arise between 400 and 1300 cm –1 . The band at 1260 cm –1 , which is for compound 2 notably intense, can be assigned to the P–O–H deformation vibration .…”
Section: Resultsmentioning
confidence: 99%
“…9). [31][32][33] Additional vibrations in the region of 1100-1200cm -1 also suggest a reduction in symmetry of the oxoanion unit. For M=Co and Cu, the spectra resulting from the fluorophosphates doped materials matched that which was obtained for the undoped Na 2 Ni(SO 4 ) 2 •2H 2 O material which naturally adopts the triclinic structure (Fig.…”
Section: Raman Data For Na 2 M(so 4 ) 2-x (Po 3 F) X •2h 2 O (M= Fe mentioning
confidence: 99%